Additive Manufacturing of Ceramics: Issues, Potentialities, and Opportunities. Issue 7 (July 2015) - Zocca, Andrea; Colombo, Paolo; Gomes, Cynthia M.; Günster, Jens; Green, D. J.
<x xml:space="preserve">Abstract</x> Additive manufacturing (AM) is a technology which has the potential not only to change the way of conventional industrial manufacturing processes, adding material instead of subtracting, but also to create entirely new production and business strategies. Since about three decades, AM technologies have been used to fabricate prototypes or models mostly from polymeric or metallic materials. Recently, products have been introduced into the market that cannot be produced in another way than additively. Ceramic materials are, however, not easy to process by AM technologies, as their processing requirements (in terms of feedstock and/or sintering) are very challenging. On the other hand, it can be expected that AM technologies, once successful, will have an extraordinary impact on the industrial production of ceramic components and, moreover, will open for ceramics new uses and new markets.